2008
DOI: 10.1007/s00203-008-0414-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced synthesis and antimicrobial activities of bacteriocins produced by Mexican strains of Bacillus thuringiensis

Abstract: Recently, we reported the synthesis of five bacteriocin-like inhibitor substances (Bt-BLIS: morricin 269, kurstacin 287, kenyacin 404, entomocin 420, and tolworthcin 524) by Mexican strains of Bacillus thuringiensis. Here we show that, collectively, these Bt-BLIS have a moderate to broad spectrum of antibacterial activity, being toxic to clinically significant against Gram-positive and Gram-negative bacteria, including common etiological agents of human diseases, such as strep throat and scarlet fever, septice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…Nisin, a bacteriocin synthesized by Lactococcus lactis is currently the only bacteriocin with use in food industry and has been employed J. E. Barboza-Corona et al for the last two decades as a food preservative. It has been shown that bacteriocins of B. thuringiensis have a wide or narrow spectrum of activity against pathogenic bacteria (Cherif et al 2008;De la Fuente-Salcido et al 2008;Rea et al 2010). Both types of activity are important and could have different uses.…”
Section: Potential Applications Of Bacillus Thuringiensis Bacteriocinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nisin, a bacteriocin synthesized by Lactococcus lactis is currently the only bacteriocin with use in food industry and has been employed J. E. Barboza-Corona et al for the last two decades as a food preservative. It has been shown that bacteriocins of B. thuringiensis have a wide or narrow spectrum of activity against pathogenic bacteria (Cherif et al 2008;De la Fuente-Salcido et al 2008;Rea et al 2010). Both types of activity are important and could have different uses.…”
Section: Potential Applications Of Bacillus Thuringiensis Bacteriocinsmentioning
confidence: 99%
“…Both types of activity are important and could have different uses. For example, bacteriocins with wide activity could be used not only as antibiotics but also as biopreservatives in the control of food-borne pathogenic bacteria ; De la Fuente-Salcido et al 2008). Entomocin 110 and Thuricin 7 could be used respectively to control Listeria monocytogenes and preventing spoilage of raw milk and dairy products caused by B. weihenstephanensis (Cherif et al 2001(Cherif et al , 2008.…”
Section: Potential Applications Of Bacillus Thuringiensis Bacteriocinsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the samples was used for monitoring cell growth spectrophotometrically at 600 nm, and the other was employed for bacteriocin detection using a rapid fluorogenic method [12], using B. cereus 183 as indicator bacterium. After determining the time that yielded the highest level of bacteriocin production, the bacterium was cultivated in fresh TSB and culture supernatant was concentrated with ammonium sulfate as described previously [12,13]. Precipitated proteins were pelleted by centrifugation at 16.000× g for 30 min at 4…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Each point of activity was repeated in triplicate and the average was recorded. For our purposes, we define one unit (U) of bacteriocin activity as equal to 1 mm 2 of the zone of inhibition of growth of the indicator bacterium [12,13].…”
Section: Antibacterial Activitymentioning
confidence: 99%